2021
DOI: 10.3892/etm.2021.11094
|View full text |Cite
|
Sign up to set email alerts
|

Lectin‑type oxidized LDL receptor 1 modulates matrix metalloproteinase 2 production in peri‑implantitis

Abstract: Peri-implantitis is a disease in which inflammatory lesions that affect the surrounding soft and hard tissues develop. Matrix metalloproteinase 2 (MMP2) is hypothesized to be involved in this destructive process. However, the regulatory mechanism of action of MMP2 in the peripheral tissues of the implant are not fully understood. To determine the expression of MMP2 in peri-implantitis, peri-implant crevicular fluid (PICF) was collected from patients with peri-implantitis. The healthy volunteers' peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Also, matrix metalloproteinase-2 (MMP-2) was found to be upregulated by LOX-1 in human macrophages infected by P. gingivalis . In this process, JNK and ERK1/2 also seemed to be involved in the LOX-1-dependent signaling process [ 113 ]. Additionally, it was found that LOX-1 is upregulated during infection in a process mediated by TLR2 and/or activation via MAPK in BMCs, which leads to osteoclastogenesis [ 123 ].…”
Section: Pathogen-specific Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, matrix metalloproteinase-2 (MMP-2) was found to be upregulated by LOX-1 in human macrophages infected by P. gingivalis . In this process, JNK and ERK1/2 also seemed to be involved in the LOX-1-dependent signaling process [ 113 ]. Additionally, it was found that LOX-1 is upregulated during infection in a process mediated by TLR2 and/or activation via MAPK in BMCs, which leads to osteoclastogenesis [ 123 ].…”
Section: Pathogen-specific Interactionmentioning
confidence: 99%
“…List of the agents interacting with LOX-1 in infections and in which cell and animal models the interaction was reported Interacting agent corneal epithelial cells, mouse corneas Upregulation, mediated by NF-κB Protein, mRNA[110,113] IL-1β Human corneal epithelial cells, mouse corneas Upregulation Protein, mRNA[113] VCAM-1 HMEC-1, HUVECs, RAW macrophages, mouse corneas Upregulation Protein, mRNA[111,112,118] E-Selectin HMEC-1, HUVECs, RAW macrophages, mouse corneas Upregulation, mediated by NF-κB Protein, mRNA[109-…”
mentioning
confidence: 99%